KAJIAN YURIDIS TERHADAP PENERAPAN PASAL 21 AYAT 1 KITAB UNDANG UNDANG HUKUM ACARA PIDANA (KUHAP) TENTANG PENAHANAN ATAU PENAHANAN LANJUTAN - Karyoto Karyoto; Oktabilla Ayu Lestari (Universitas Islam Kadiri, 2019)
because suspects or defendants are particularly vulnerable to violations of their human rights, especially in the context of law enforcement. The suspect or defendant is in the position of the examination object in the process. All series of processes, whether in the examination phase of witnesses, expert examinations, evidence collection, and other evidence collection, are directed to a suspect or defendant, either to convict or not to be guilty The aims of this study are: (1) To know the meaning of the obscurity of the norm in the sentence